Anticoagulation in device-detected atrial fibrillation: Challenges in stroke prevention and heart failure management - Vrtal, Jiri; Plasek, Jiri; Vaclavik, Jan; Dodulik, Jozef; Sipula, David (Biomedical papers, 2025)
Atrial fibrillation (AF), the most common cardiac arrhythmia globally, contributes significantly to morbidity and mortality. With advancements in implantable devices like pacemakers, defibrillators, and loop recorders, incidental detection of AF as device-detected AF (DDAF) or subclinical AF (SCAF) has become common. This asymptomatic AF presents unique management challenges, particularly in anticoagulation decisions for stroke prevention. Evidence from recent trials, notably NOAH-AFNET 6 and ARTESiA, indicates a complex risk-benefit profile for anticoagulation in DDAF. In ARTESiA, anticoagulation modestly reduced stroke and systemic embolism rates, though this effect did not reach statistical significance. The NOAH-AFNET 6 trial found no significant reduction in a composite of cardiovascular death, stroke, or systemic embolism with anticoagulation compared to placebo. Both trials revealed an increased bleeding risk, underscoring the need to carefully weigh stroke prevention against bleeding risks in DDAF. The 2024 European Society of Cardiology guidelines reflect this nuanced approach by advocating a tailored, risk-based strategy. Emerging evidence also shows that AF burden impacts heart failure (HF) outcomes, with a five-fold increase in HF hospitalizations associated with higher AF burden. This highlights the importance of rhythm or rate control to reduce HF progression, particularly in patients with both AF and HF, where reducing AF burden is associated with better prognosis and fewer hospitalizations. Future research should focus on refining anticoagulation strategies, especially for patients with low AF burden, and exploring novel approaches like intermittent anticoagulation and advanced monitoring to support personalized DDAF management.
Keywords: atrial fibrillation; device-detected atrial fibrillation; stroke; anticoagulation; heart failure